Implementasi Jaringan Syaraf Tiruan Metode Backpropagation untuk Prediksi Penjualan Mobil Bekas - Prima Dina Atika; Rasim Rasim (Jurnal ICT : Information Communication & Technology, 2019)
Increased sales are needed in line with the rapid economic growth in Indonesia. Procurement of goods and services is an activity needed to realize developments in the area. Manually predictive calculations have a high level of risk and hinder the sales performance process. To handle this, a system is needed to be able to calculate the predictions of the number of used cars sold and reduce the risk of very heavy losses. With the application of this prediction system, it is expected to overcome these problems. The method used is the Backpropogation Method, a training method that uses multilayer perceptron to solve complex problems with supervised training methods, namely pairs that use input-output and which will be calculated is the weight, the desired output target. With the method of Backpropagation Artificial Neural Network (ANN) calculation. The results show that the application system created can produce predictive results that are accurate enough to get results that are not much different from actual sales, ie with MSE = 23.84.